Analisis Pengaturan Hukum Pidana terhadap Penyalahgunaan Teknologi Manipulasi Gambar (Deepfake) dalam Penyebaran Konten Pornografi Melalui Akun Media Sosial - Olivia Novera; Fitri.Z, Yenny (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2024)
Deepfake is an advanced technology that utilizes the latest artificial intelligence techniques to produce compelling images or motion pictures that appear to be genuine. This technique uses specialized algorithms to create fake content that is difficult to distinguish from the real thing. In Indonesia, cases of deepfake pornography have increased in recent years. With this new Artificial Intelligence technology which in addition to the many positive impacts it provides, it also has negative impacts that can support the occurrence of these cases. the spread of pornographic content with image manipulation (deepfake) has become one of the negative impacts of this technology. This study aims to determine the shortcomings in the legal arrangements and how they are implemented in cases of deepfake, or the misuse of AI technology. The research method used is normative legal research based on literature and laws and regulations. This research found that several general and specific rules relating to the misuse of deepfake technology through social media have not covered all aspects of image manipulation (deepfake) containing pornography on social media accounts. Therefore, although pornographic deepfake cases often occur and harm some people, the limited legal regulation of these acts causes the legal apparatus to have difficulty in ensnaring the perpetrators.